Higgs- and Goldstone-boson-mediated long range forces - Ferrer, F.; Nowakowski, M. [UNESP] (American Physical Society (APS), 1999)
In certain mild extensions of the standard model, spin-independent long range forces can arise by exchange of two very light pseudoscalar spin-0 bosons. In particular, we have in mind models in which these bosons do not have direct tree level couplings to ordinary fermions. Using the dispersion theoretical method, we find a 1/r3 behavior of the potential for the exchange of very light pseudoscalars and a 1/r7 dependence if the pseudoscalars are true massless Goldstone bosons. ©1999 The American Physical Society.